White House School. - Owoo, Betty (Architectural Review, 2024)
vPPR Architects has designed an addition to the White House Preparatory School in London, which is housed in a historic Italianate villa. The new building includes a multipurpose hall, classrooms, and other spaces for students and the school community. The design incorporates natural finishes, maximizes natural light, and blends in with the surrounding residential context. The project faced challenges due to limited resources and a tight timeline, but it has been successful in transforming the school and providing new services and activities. The article also highlights the need for investment in state-funded schools and the potential benefits of engaging design-led practices in the public sector.